Highly Efficient Electrocatalytic Upgrade of n‐Valeraldehyde to Octane over Au SACs–NiMn2O4 Spinel Synergetic Composites. Issue 30 (29th June 2022) - Qin, Meichun; Fan, Shiying; Li, Xinyong; Niu, Zhaodong; Bai, Chunpeng; Chen, Guohua
Abstract: In this work, electrocatalytic upgrade of n ‐valeraldehyde to octane with higher activity and selectivity is achieved over Au single‐atom catalysts (SACs)–NiMn2 O4 spinel synergetic composites. Experiments combined with density functional theory calculation collaboratively demonstrate that Au single‐atoms occupy surface Ni 2+ vacancies of NiMn2 O4, which play a dominant role in n ‐valeraldehyde selective oxidation. A detailed investigation reveals that the initial n ‐valeraldehyde molecule preferentially adsorbs on the Mn tetrahedral site of NiMn2 O4 spinel synergetic structures, and the subsequent n ‐valeraldehyde molecule easily adsorbs on the Ni site. Specifically, Au single‐atom surficial derivation over spinel lowers the adsorption energy ( E ads ) of the initial n ‐valeraldehyde molecule, which will facilitate its adsorption on the Mn site of Au SACs–NiMn2 O4 . Furthermore, the single‐atom Au surficial derivation not only alters the electronic structure of Au SACs–NiMn2 O4 but also lower the E ads of subsequent n ‐valeraldehyde molecule. Hence, the subsequent n ‐valeraldehyde molecules prefer adsorption on Au sites rather than Ni sites, and the process of two alkyl radicals originating from Mn–C4 H9 and Au–C4 H9 dimerization into an octane is accordingly accelerated. This work will provide an avenue for the rational design of SACs and supply a vital mechanism for understanding the electrocatalytic upgrade of n ‐valeraldehyde to octane. Abstract : The electrocatalytic upgrade of n ‐valeraldehyde to octane with higher activity and selectivity is achieved over Au single‐atom catalysts (SACs)–NiMn2 O4 spinel synergetic composites. Experiments combined with density functional theory calculation collaboratively demonstrate that Au single atoms occupy surface Ni 2+ vacancies of NiMn2 O4, which facilitates the adsorption of n‐ valeraldehyde molecules and further lowers the energy barrier of the rate‐determining step.